Optimization and Simulation of Loading and Unloading Robot Structure Parameter of Production Line - Chuan Liao; Yinghua Liao; Jun Xie (Jixie chuandong)
Production line layout planning is closely related to robot structural parameter. For the intelligent production line of the headstock of a vertical machining center， in order to complete the work requirements of grabbing and flipping the workpiece， and reducing the operating space and structure size of the robot， a structural parameter optimization method for loading and unloading robots is proposed. The working space is a constraint condition， and the optimal section of the main section of the manipulator workspace is the objective function， and the structural parameter optimization model is established. Finally， the Monte Carlo method is used to verify the workspace. The results show that the size of the optimized robot workspace is significantly lower than other design schemes under the requirements of the loading and unloading workspace， which reduces the redundant waste of the workspace and further reduces the workload. The foundation of the design research of loading and unloading robot is laid.